Dual improvement of DNA-directed antibody immobilization utilizing magnetic fishing and a polyamine coated surface. Issue 112 (23rd November 2016) - Esmaeili, Elaheh; Soleimani, Masoud; Shamloo, Amir; Mahmoudifard, Matin; Vossoughi, Manouchehr
Abstract : The magnetic improvement of DNA-directed antibody immobilization in terms of a highly efficient sensing platform for anti-prostate-specific membrane antigen immobilization has been reported. Abstract : The present study is aimed at the development of a novel approach based on the magnetic improvement of DNA-directed antibody immobilization to prepare a highly efficient sensing platform. Magnetic nanoparticle substrates with high surface area capture the dual DNA-conjugated antibodies in a solution. This allows overcoming the typical mass transport limitation of the surface-based antibody immobilization. Antibody-magnetic nanoparticle conjugation is based on a robust hybridization between a DNA tether (attached to the antibody) and its complementary sequence (immobilized on the nanoparticle). Conventional antibody immobilization for the detection of proteins is often insignificant for the preservation of the folded antibody conformations due to the surface-induced denaturation or drying and dehydration. In this study, a biosensor platform is designed and fabricated by DNA-directed immobilization to maintain the antibody functionality. Also, DNA coated surfaces have advantages of greater stability, a variety of strands, and specificity of DNA base pairs. In principle, this allows the multiplexed detection of proteins within the same surface area. Thus, this attractive approach with DNA-directed antibody immobilization using a poly-l -lysine coated surface with highly pre-adsorbed ssDNA, along with magnetic nanoparticles to increase the surface concentration of the biomolecules, is promising for the utilization in, and the improvement of, surface-based biosensors. Our findings suggest that this method will be effective in a variety of biomedical applications, such as cell separation, diagnosis, and monitoring of human diseases.